The attractiveness of jobs in the German care sector: Results of a factorial survey - Martin Kroczek; Jochen Späth (Institut für Angewandte Wirtschaftsforschung (IAW), 2020)
The skilled labour shortage in nursing is an issue not unique to Germany. Unattractive characteristics of nursing jobs are one reason for the low supply in nursing personnel. In our study, we analyse the influence of job characteristics on the attractiveness of nursing jobs. We address this issue via factorial survey analysis, an experimental method particularly suited to assessing personal opinions and less prone to social desirability bias than standard interview methods. Around 1,300 (current and former) nurses in a distinct region in Germany were asked to rate a set of synthetic job postings, each of which contained information on nine systematically varied job characteristics. We find that, first, attractiveness of care jobs is most strongly affected by rather "soft" characteristics such as atmosphere within the team and time for patients. "Hard" factors play a considerably smaller role. Second, one hard factor, contract duration, is estimated to be among the most important job factors, however. This is a remarkable finding given that nursing occupations suffer from severe skill shortages. Third, though wage has a statistically significant influence on attractiveness, enormous wage raises would be needed in order to yield higher attractiveness gains than the top-rated soft factors, or to compensate for less pleasant job characteristics with respect to those factors. Last, even after controlling for other job characteristics, hospital nursing is still rated as more attractive than geriatric nursing.
Keywords: I11; J44; J22; 330; Nurse; Labour Supply; Job Choice